Marmaduke Pickthall Islam and the Modern World : - Nash, Geoffrey P. (Brill, 2016)
This new volume of essays marks eighty years since the death of Marmaduke Pickthall. His various roles as translator of the QurÊ¾an, traveller to the Near East, political journalist writing on behalf of Muslim Turkey, and creator of the Muslim novel are discussed. In later life Pickthall became a prominent member of the British Muslim community in London and Woking, co-worker with Muslims in the Indian subcontinent, supporter of the Khilafat movement, and editor of the journal Islamic Culture under the patronage of the Nizam of Hyderabad. Marmaduke Pickthall: Islam and the Modern World makes an important contribution to the field of Muslims in Europe in the first half of the twentieth century.